The jurisgenesis of Human Rights: a signifier pursued by its signified, between 1945 and 1993 - ALMEIDA, Miguel Régio de (Revista Jurídica Portucalense, 2022)
In a short essay, of an especially pedagogical nature, I aim to put in context the genealogy of the signifier «Human Rights». This will be done through an anticolonialist and antiracist lens, framed within the Critical Legal Studies academical Movement. Naturally, the omphalic point is the Charter designed in the 1945 San Francisco Conference, where the signifier appeared for the first time. However, the moment of plenitude is to be found in the 1993 World Conference on Human Rights, in Vienna, where the signifier finally became legitimately aligned with its own signified. Between the two temporal milestones, there was a seminal activity inside and outside the UN stages, protagonized by agents once subalternized. An activity that only recently came to the spotlight – and to which this essay also sheds some more light. It will become clear that to review the jurisgenesis of «Human Rights» is not a simple exercise of memory. On the contrary, it is a firm and indispensable step towards the formation of the International Law yet to come – the one that will have to answer to the new challenges faced by Humanity. A Humanity seen in its totality, without the legal orientalism that hegemonically tainted this field.